Exploration of nano sized defects in Fe2O3 doped lead zirconium silicate glass ceramics by using positron annihilation lifetime spectroscopy. Issue 15 (1st August 2021) - Kostrzewa, M.; Siva Sesha Reddy, A.; Ingram, A.; Smirnov, Anton; Ravi Kumar, V.; Veeraiah, N.
Abstract: This work is focused on the evaluation of the free volume space and the concentration of nano-sized cavities trapped in Fe2 O3 mixed lead zirconium silicate glass ceramics using positron annihilation lifetime spectroscopy (PALS) studies with 22 Na (0.1MBq) positron source. Such imperfections are anticipated to have strong bearing on physical characteristics of the glass ceramic. The glasses of a particular composition viz ., 36PbO–4ZrO2 –(60– x )SiO2 : x Fe2 O3 (0 ≤ x ≤ 0.5 in the intervals of 0.1) were synthesized by traditional melting and quenching techniques. The lifetime of the positrons measured in these samples is found to be strongly reliant on the content of Fe2 O3 . The results have suggested the increased fraction of free volume imperfections ( f v ), and radius of the cavities ( R ) with increase of Fe2 O3 content from 0.2 to 0.5 mol%. The spectroscopic studies of these samples indicated that iron ions predominantly existed in Fe 3+ state and occupied octahedral positions with FeO6 structural units, acted as modifiers and induced several imperfections. The estimated maximal concentration of imperfections in the glass ceramic sample F5 by PALS studies is attributed to such reasons. The inferences drawn from PALS studies regarding the concentration of defects in these samples are found to be in agreement with the results of third harmonic generation (THG) studies and conductivity studies.